2017
DOI: 10.4236/ojog.2017.72017
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depression and Mother-to-Infant Bonding: The Association of Delivery Mode, General Health and Stress Markers

Abstract: Aim: The aim of the present study was to examine associations among maternal stress level, general health, mother to infant bonding, maternal depression level, and mode of delivery. Methods: Mothers who delivered a single baby at term were recruited with a total 435 mothers participating in the study. Outcome measures: Data were collected 6 months after delivery using General Health Questionnaire (GHQ-28), Mother-to-Infant Bonding Scale (MIBS), Edinburgh Postnatal Depression Scale (EPDS) as well as socio-demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…At 14 months postpartum, no category of the MOD had a direct effect on parent-infant-bonding among fathers. Apparently, these findings are contradictory to previous research, finding either no association between the MOD and mother-infant-bonding [ 26 29 ] or indeed weaker mother-infant-bonding in mothers giving birth by CS compared to spontaneous VD [ 30 , 31 ]. An explanation to our findings might be compensatory behaviors that parents, whose baby was delivered via unplanned CS, engage in to mitigate potential negative impacts for the infant.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…At 14 months postpartum, no category of the MOD had a direct effect on parent-infant-bonding among fathers. Apparently, these findings are contradictory to previous research, finding either no association between the MOD and mother-infant-bonding [ 26 29 ] or indeed weaker mother-infant-bonding in mothers giving birth by CS compared to spontaneous VD [ 30 , 31 ]. An explanation to our findings might be compensatory behaviors that parents, whose baby was delivered via unplanned CS, engage in to mitigate potential negative impacts for the infant.…”
Section: Discussioncontrasting
confidence: 96%
“…For instance, a prospective study contrasting CS and vaginal delivery showed that women who had an unplanned CS reported weaker bonding [ 30 ]. Similarly, Ishii et al [ 31 ] found that women who had a vaginal delivery reported stronger mother-infant-bonding than women who underwent a planned CS. Also, a qualitative study interviewing women who had an unplanned CS reported an interruption of the initial bond between mother and infant and a feeling of disconnectedness due to the separation after childbirth [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, parents often involuntarily miss out on having a natural birth experience to promote the safety of mother and child. Studies indicate that CD can negatively impact short-term and long-term birth satisfaction, bonding, and breast feeding [4][5][6][7][8][9]. Investigations of the association between delivery mode and postpartum maternal mental health have yielded contradictory results [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to form or express social bonds also can be disrupted by events that alter the oxytocin and vasopressin systems. Data from animal models and human epidemiology suggest that routine medical interventions (for example, oxytocin [Pitocin] use to induce labor, opioid medications that block the oxytocin system, or caesarean sections that alter exposure to endogenous oxytocin) have lasting consequences for the offspring and/or mother (Hayes, Balaban, Smith, Perry-Jenkins, & Powers, 2010;Kroll-Desrosiers et al, 2017;Song et al, 2017). Our ongo-ing animal research suggests that such exposures could have epigenetic efects on the oxytocin systems, including changes in DNA methylation.…”
Section: Sources Of Individual Differencesmentioning
confidence: 99%